Desmond and the very mean word : a story of forgiveness - Tutu, Desmond; Abrams, Douglas Carlton (Candlewick Press, 2013)
When Desmond takes his new bicycle out for a ride, his pride and joy turn to hurt and anger when some boys shout a very mean word at him causing Desmond to seek the advice of Father Trevor, who teaches him about the power of forgiveness.